Florida 4-H Secretary Record Book - Sarah Thomas Hensley; Stacey Ellison (EDIS)
The Florida 4-H Secretary record book will provide the club secretary with an official outline for tracking all club records. This 30-page book serves as a guide and should be completed annually by the 4-H club secretary. This major revision was written by Sarah Thomas Hensley and Stacey Ellison and published by the UF/IFAS Extension 4-H Youth Development program. http://edis.ifas.ufl.edu/4h011